Haiti : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper analyzes Haiti's external competitiveness. The analysis shows that the country has been experiencing equilibrium real exchange rate appreciation pressures, which have originated more recently from the rising inflow of transfers. The paper discusses avenues for further developing Haiti's monetary policy framework to help consolidate a stable low-inflation environment and support deepening domestic financial markets. The analysis suggests that Haiti's monetary policy regime could be strengthened through a two-step approach. The paper also focuses on options to increase domestic revenues as a means of funding priority expenditures.